(untitled) (International Journal of Food and Nutritional Sciences, 2022)
India is experiencing rapid industrialisation phase. The most important concern of any industry is to do business profitably. The profit making requires identification of factors to be controlled and monitored. An explorative research is done to make instruments i.e. questionnaire for data collection. The purpose of questionnaire is to obtain information to improve its content, format and sequence. The study identifies critical factors responsible for the growth of small scale industries. Various elements related to Quality, productivity, safety, risk, return on investment are identified for enhanced organisational performance.